Burden and severity of disease of aromatic L-amino acid decarboxylase deficiency: a systematic literature review. (2nd November 2022) - Buesch, Katharina; Zhang, Rongrong; Szczepańska, Katarzyna; Veličković, Vladica; Turner, Lucy; Despotović, Milena; Đorđević, Branka; Russell, Alexis
Abstract: Objective: The objective was to investigate the severity of aromatic L-amino acid decarboxylase deficiency (AADCd) as reported in the published literature and to collate evidence of the clinical manifestations of AADCd, and the impact of the disease on patients, caregivers, and healthcare systems. Methods: Published articles reporting severity of disease or disease impact were eligible for inclusion in this review. Articles were searched in MEDLINE, EMBASE, Cochrane CENTRAL, TRIP medical, and CRD databases in October 2021. The quality of the included studies was investigated using a modified version of the grading system of the Centre for Evidence-Based Medicine (CEBM). Descriptive data of the literature was extracted and a narrative synthesis of the results across studies was conducted. This review is reported according to the PRISMA reporting guidelines for systematic reviews. Results: The search identified 970 unique reports, of which 59 met eligibility criteria to be included in the review. Of these, 48 included reports provided details on the clinical manifestations of AADCd. Two reports explored the disease impact on patients, while four described the impact on caregivers. Five reports assessed the impact on healthcare systems. Individuals with AADCd experience very severe clinical manifestations regardless of motor milestones achieved, and present with a spectrum of other complications. Individuals with AADCd present with very limited function, which, in combination with additional complications, substantially impact the quality-of-life of individuals and their caregivers. The five studies which explore the impact on the healthcare system reported that adequate care of individuals with AADCd requires a vast array of medical services and supportive therapies. Conclusions: Irrespective of the ambulatory status of individuals, AADCd is a debilitating disease that significantly impacts quality-of-life for individuals and caregivers. It impacts the healthcare system due to the need for complex coordinated activities of a multidisciplinary specialist team.